If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4(z + 3) + 5 = 7z + 26 Reorder the terms: -4(3 + z) + 5 = 7z + 26 (3 * -4 + z * -4) + 5 = 7z + 26 (-12 + -4z) + 5 = 7z + 26 Reorder the terms: -12 + 5 + -4z = 7z + 26 Combine like terms: -12 + 5 = -7 -7 + -4z = 7z + 26 Reorder the terms: -7 + -4z = 26 + 7z Solving -7 + -4z = 26 + 7z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-7z' to each side of the equation. -7 + -4z + -7z = 26 + 7z + -7z Combine like terms: -4z + -7z = -11z -7 + -11z = 26 + 7z + -7z Combine like terms: 7z + -7z = 0 -7 + -11z = 26 + 0 -7 + -11z = 26 Add '7' to each side of the equation. -7 + 7 + -11z = 26 + 7 Combine like terms: -7 + 7 = 0 0 + -11z = 26 + 7 -11z = 26 + 7 Combine like terms: 26 + 7 = 33 -11z = 33 Divide each side by '-11'. z = -3 Simplifying z = -3
| -4(z+3)+5=7z+6 | | 6(x+2)=11 | | n-.6n=32 | | 19=4+5t | | n-.06=32 | | 2x^3+32=3x^3-32 | | y-3=-17+4 | | 3y=12x+6 | | 15x^4+14x^2-8=0 | | 2.5x-3.5=6.5 | | X^2-2=5x | | 12=48x^2 | | 2/3x=6-x | | 3/5×2/3= | | 20×-2/3 | | 80.18=y^2+15y | | 4n-5n=39-43 | | 81=x^2+17.3x | | 3(2x-7)=3(3x-5) | | 17y-9+4y=21x-3+5x+1 | | 3y+39=-9(y-7) | | 115x(1.00-x)(2.00-x)=4x^2 | | 115x(1.00-x)(2.00-x)=4x | | 3x^10/27x^7 | | 9y+4=2y+26 | | 4x^2+9x-210=0 | | 3y/2-2=x=y/6-2/3. | | i+x= | | xi= | | (3,9);m=-1/4 | | E^3x-4=1 | | 6sin(x)=0 |